Vincent Tewson (1946)
1946 1945-1960 "Vincent Tewson" [hfr0193], 1946 Vincent Tewson (1898-1981) was born in Bradford and joined the TUC in 1925 as Secretary of the Organisation Department. He became Assistant General Secretary in 1931 and was General Secretary 1946-1960. He was a member of the post war tripartite Economic Planning Board under Lord Plowden.